The impact of moderate distance recreational running and ageing on cardiac physiology. Issue 3 (16th August 2016) - Kim, Jonathan H; Ko, Yi-An; Hedley, Jeff; MacNamara, James; Awad, Mosaab; Taylor, William; Healy, Sean; Aida, Hiroshi; Le, Ngoc-Anh; Wilson, Peter W; White, Melissa; Sperling, Laurence S; et al.
Abstract : Objective: Exercise-induced cardiac dysfunction and corollary biomarker release have been documented following long-distance running events. To what degree these processes occur during shorter distance running events is unknown. Methods: 72 healthy recreational runners (54% male/46% female) recruited by age (group 1 (18–20 years old, N=19); group 2 (45–50 years old, N=27); group 3 (70–75 years old, N=26)) were studied with echocardiography and biochemical profiling during participation in a 10 km running race. Results: Despite age-dependent baseline differences in ventricular size and diastolic tissue velocities, there were no significant within group or across group decrements in ventricular systolic or diastolic function following race completion. Postrace increases in cardiac troponin-I (cTnI), B-type natriuretic peptide (BNP) and high-sensitivity C-reactive protein (hs-CRP) were common and demonstrated distinct age dependent profiles. Specifically, BNP increases were most pronounced among older runners (group 3Δ: 16±22 pg/mL, p=0.001), hs-CRP increased only among younger runners (group 1Δ: 1.5±2.7 mg/L, p=0.03) and cTnI increased in both younger (group 1Δ: 0.01±0.02 ng/mL, p=0.028) and older (group 3Δ: 0.01±0.01 ng/mL, p=0.007) runners, but not middle aged runners (group 2Δ: 0.00±0.00 ng/mL, p=0.57). Conclusions: Moderate distance recreational running leads to distinct age-dependent biomarker release but is not associated with cardiac fatigue, a proposed stimulus for pathologic cardiac remodelling that has been observed following longer distance running events.